Tuning a magnetic energy scale with pressure and field in UTe2 - Hyunsoo Kim; I-Lin Liu; Wen-Chen Lin; Yun Suk Eo; Sheng Ran; Nicholas P. Butch; Johnpierre Paglione (Communications Materials, 2025)
Abstract When a fragile ordered state is suppressed to zero temperature, a quantum phase transition occurs, which is often marked by the appearance of unconventional superconductivity. While the quantum critical point can be hidden, the influence of the quantum criticality extends to fairly high temperatures, manifesting non-Fermi liquid behavior in a wide range of the field-temperature-pressure phase space. Here, we report the tuning of a magnetic energy scale in the heavy-fermion superconductor UTe2, previously identified with a peak in the c-axis electrical transport temperature dependence, using applied hydrostatic pressures and a-axis-oriented magnetic fields as complementary (and opposing) tuning parameters: the characteristic peak in c-axis resistivity decreases in temperature with applied pressure before vanishing near the critical pressure of 15 kbar (1.5 GPa), while the application of field shifts the peak to a higher temperature and broadens it under all studied pressures. At the critical pressure, the transport behavior deviates from Fermi liquid behavior, exhibiting a nearly linear temperature dependence of resistivity with an enhanced pre-factor. Our results shed light on the microscopic origin of the c-axis resistivity peak and provide a clear picture of magnetic energy scale evolution relevant to quantum criticality in UTe2.